ANALISIS HUBUNGAN ANTARA CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Arfian Kurnia Pratama; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the relationship of corporate social responsibility (CSR) on earnings management and the impact of audit fee and audit firm size on the association between corporate social responsibility (CSR) and earnings management. The dependent variable that used in this study is earnings management. Corporate social responsibility (CSR) used as independent variable. Furthermore, this study used audit fee and audit firm size as a moderating variable. The sample in this study consists of 164 manufacture companies that listed on Indonesia Stock Exchange in the period 2017-2018. The data that used in this study was secondary data and selected by using purposive sampling method. The technique of analysis used for examining the hypothesis was multiple regression analysis Based on the empirical results of this study show that corporate social responsibility (CSR) has positive not significant influence on earnings management. This study did not find the association of audit fee between corporate social responsibility (CSR) and earnings management, but this study found the association of audit firm size between corporate social responsibility (CSR) and earnings management.